Performance Evaluation Of Area Cleanliness Company Using Balanced Score Card (Analytical Study Of Waste Management In Bandung City) - Wargadinata, Betty; Sulaeman, Eman; Prasetyo, Riyan; Wahyudin, Restu Budi; Siregar, Syahdias (STKIP Yapis Dompu, 2022)
In the current era of globalization, every business entity, including PD Cleaning needs to be managed professionally. For this reason, improving organizational performance, alignment of organizational goals and individual goals is very important. For this reason, a comprehensive performance appraisal system is needed. The Balanced Scorecard is an alternative performance measurement that combines financial and non-financial performance measures. This measurement is the result of a process based on the mission and strategy of a company. This study aims to determine how the performance of PD Hygiene, using the concept of the Balanced Scorecard, by measuring four aspects, namely financial perspective, customer perspective, internal business process perspective, learning and growth perspective. From the research results it is known that, the learning and growth perspective shows that employee productivity is still low, the percentage of skilled employee training every year is still low. This triggers the level of employee satisfaction is still not satisfied. Internal business perspective, the level of service has not satisfied customers.